Understanding Wearable Device Adoption: Review on Adoption Factors and Directions for Further Research in Smart Healthcare - Hossain M.I.; Yusof A.F.; Shanmugam M. (Springer Science and Business Media Deutschland GmbH, 2023)
Blood; Glucose; Internet of things; Wearable technology; Adoption factors; Adoption model; Blood glucose; Blood glucose monitoring; Paper analysis; Smart healthcare adoption; Smart wearables; Trustworthiness; Wearable devices; Wearable healthcare device; Health care